Singapore : 2012 Article IV Consultation; Staff Report, Informational Annex, Public Information. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Singapore's large financial sector has remained resilient. The output has shown to rebound strongly despite a drop of 9 percent in GDP during 2008-early 2009. The new challenges include consumer price inflation, income inequality, and rising housing prices. The downside risks for the Singapore economy are large, but the country has large buffers and significant policy room to dampen the immediate and longer-term effects of a sharp global slowdown. The authorities have ample policy space and instruments to address the negative impact of economic shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet